Analysis Readiness School In Implementation Of Inclusive Education In Malang City - Dessy Putri Wahyuningtyas; Nur Rohmah Nilam Sari; Surayanti Surayanti; Wiryanto Wiryanto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Inclusive education is an effort to implement education with students with disabilities and non-disabled students as a form of justice, equality and the realization of human rights in the field of education. The low participation of children with disabilities in the learning process is very low due to limited physical and social abilities. The aim of this research is to study, analyze and evaluate the inclusive education delivery system in Malang City at the elementary, middle and high school levels. This research used a survey method with a quantitative approach carried out in Malang City, East Java. The population of this research was all inclusive schools in Malang City, totaling 160 schools. Based on the results of the analysis of questionnaire data distributed to respondents, it shows that the key to the success of educational units providing inclusive education is the readiness of teachers and disability-friendly infrastructure which is a significant benchmark for interventions to minimize barriers to learning for students with disabilities in order to realize learning flexibility, in addition to the support of students' parents. Disability is also a major supporting factor for educational units